ChemInform Abstract: Synthesis and Properties of Molybdenum Disulfide: From Bulk to Atomic Layers. Issue 14 (April 2015) - Song, Intek; Park, Chibeom; Choi, Hee Cheul
Abstract: Review: synthesis, structural polytypes, properties, and application of bulk, multi‐ and single‐layer MoS2 ; 205 refs.